Metodología de evaluación del sitio para la Disposición final de los desechos sólidos. - Morocho Rojas, Leoner Johnson (2017)
The evaluation of sites for the final disposal of solid wastes generated by large cities is important because it is directly related to the good living of its inhabitants, in this sense the physical, operational, sanitary and environmental characteristics are the areas that are Should study to determine the relevance or otherwise of the proper functioning of these sites or places. To determine the physical characteristics of the site, it is important to investigate the area and location of the site, constructions, number and capacity of cells, availability of material for filling, soil permeability, road access system to the site. In order to determine the operational characteristics, the existence of technical specifications, quantity and type of waste entering, waste management, drainage, geotechnical monitoring, maintenance, area security and administrative management should be investigated.